ANALISIS CAMPUR KODE DALAM ALBUM HAVI HARDIANO - Helmi, Jenilia; Makan Malay, Naranto; Djawa, Alex (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
This research aims to describe the forms of code mixing and the factors that couse code mixing in Havi Hardiano’s albums. The data used in this research is written data and oral in the form of song lyrics. This research uses a descriptive method with a qualitative approach. The data collection technique in this research used skillful free-involed listening and note-takingtechniques. The research results obtained are that there forms of code mixing in Havi Hardiano’s album, word from code mixing, phrase from code mixing and clause from code mixing. Meanwhile, there are three factors that couse code mixingnamely, habitual factors in language use, harmony factors in song content and poet background factors. Keywords: Code Mixing, Forms, Factors.